Prevalence Rates of Sexual Behaviors, Condom Use, and Contraception Among Australian Heterosexual Adolescents. Issue 12 (16th September 2020) - Fisher, Christopher M.; Kauer, Sylvia; Mikolajczak, Gosia; Ezer, Paulina; Kerr, Lucille; Bellamy, Rosalind; Waling, Andrea; Lucke, Jayne
Abstract: Background: The development of effective health promotion practices and education programs to reduce rates of sexually transmitted infections and unintended pregnancy requires accurate, up-to-date information about young people's sexual behaviors. Aims: To provide prevalence rates on sexual behaviors and condom and contraceptive use for Australian year 10–12 heterosexual students in a nationally representative sample. Methods: A nationally representative sample of 2, 301 male and 2, 055 female year 10 through 12 heterosexual students were recruited to an online survey about their lifetime sexual behaviors and condom and contraceptive use. Means and 95% confidence intervals of weighted data, based on the national census, were reported. Outcomes: The main outcomes of this study were prevalence of sexual behaviors by gender (excluding trans and gender diverse) and prevalence of contraception and condom use among sexually active students by gender. Results: The most common sexual behavior was masturbation (96.3% of male students, 78.9% of female students), and the least common behavior was anal or vaginal sex (43.7% of male students, 48.5% of female students). Of the sexually active students, condoms were used by 78.1% of male students and 77.5% of female students at first sexual experience and by 65.1% of male students and 56.8% of female students at their most recent sexual experience, whereas 91.6% of male students and 92.3% of female students used some form of contraception at most recent sexual experience. Clinical Translation: Results provide up-to-date information on the practices clinicians who are likely to encounter with heterosexual cisgender adolescent populations in Australia. Strengths & Limitaitons: The study represents the largest representative cohort of adolescents in Australia to date. However, comparisons with previous representative studies were limited owing to differing samples by age and culture. Conclusions: Compared with earlier Australian studies, young heterosexual cisgender people today engage in slightly less oral and penetrative sexual behaviors, with the exception of more women receiving oral sex, and are generally consistent in condom and contraceptive use.